Study of Air Quality at One of the World’s Most Densely Populated City Dhaka and its Suburban Areas (Journal of Bangladesh Academy of Sciences, 2019)
Air borne particulate matter PM10 and PM2.5 were collected by using Mini Vol portable Air Sampler from the world most densely populated city Dhaka and its suburban areas over a period of January through December in 2016. This study revealed a comparison of atmospheric particulate matter (PM) of a highly polluted urban area to its two neighboring areas that accommodate heavy oil based power plants. In all three sites the quantity of PM decreases in summer reaching its lowest level in the month of July, however, it increases significantly in winter season. Despite the presence of the fuel based power plants the average concentrations of PM10 and PM2.5 at the city Dhaka surpasses its two neighbors Manikganj and Nawabganj. Interestingly, PM2.5/PM10 ratio is higher at the suburban areas than urban area. The study shows that for all the sites PM2.5 is approximately twice than that of WHO and USEPA. However, the values of PM2.5 is almost similar for Nawabganj and Manikganj but much higher for the Dhaka city especially during dry season . The Mass concentration of Black Carbon (BC) was also determined from the PM samples from Manikganj and Nawabganj.Journal of Bangladesh Academy of Sciences, Vol. 43, No. 1, 59-66, 2019